Correlation vs. causality in stock market comovement - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper seeks to disentangle the sources of correlations between high-, mid- and low-cap stock indexes from the German prime standard. In principle, such comovement can arise from direct spillover between the variables or due to common factors. By standard means, these different components are obviously not identifiable. As a solution, the underlying study proposes specifying ARCH-type models for both the idiosyncratic innovations and a common factor, so that the model structure can be identified through heteroscedasticity. The seemingly surprising result that smaller caps have higher influence than larger ones is explained by asymmetric information processing in financial markets. Broad macroeconomic information is shown to enter the common factor rather than the segment-specific shocks.
Keywords: C32; G10; 330; Identification; Spillover; Common Factor; Structural EGARCH; DAX; Börsenkurs; Aktienindex; Marktsegmentierung; Spillover-Effekt; Korrelation; Kausalanalyse; Deutschland